Utilisation of midline catheters in palliative care - Latos, Maciej; Kosson, Krzysztof (Medycyna Paliatywna/Palliative Medicine, 2024)
Continuation of intravenous therapy is an important aspect of improving quality of life in chronic or palliative patients, because current medical measures make it possible to relieve physical symptoms in many cases. Expected therapy over 5 days, combined with difficult intravenous access, indicates the possibility of using midline catheters (MCs) in a group of patients who do not have a long-term vascular port implanted. Obtaining intravenous access with MCs reduces the pain associated with numerous cannulation attempts, thus increasing patient comfort. Catheter-related complications are often secondary to poor maintenance, so proper catheter care is key to MC maintenance. Proper infusion care by properly trained staff can reduce the incidence of complications, because MCs are exposed to a number of mechanical complications compared to other types of vascular access.